2020
DOI: 10.1002/fsn3.1491
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of Escherichia coli isolated from retail foods in northern Xinjiang, China

Abstract: To determine antimicrobial resistance, 431 samples of retail foods purchased at different supermarkets in Northern Xinjiang were examined in this study. There were 112 Escherichia coli strains that were isolated, with approximately 26% of the samples contaminated by E. coli. The detection rate of E. coli isolated from pork was the highest (59.6%), followed by mutton (52.6%), retail fresh milk (52.4%), duck (36.4%), beef (35.3%), chicken (33.3%), and ready-to-eat food (12.9%); the E. coli detection rate for fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
(31 reference statements)
1
7
1
Order By: Relevance
“…Antibiotic resistance in E. coli is of particular concern because it is the most common Gram-negative bacterial pathogen causing intestinal and extra-intestinal infections in humans [ 48 ]. Apart from Gram-negative bacterial pathogens, fresh produce contaminated with Gram-positive bacteria, such as Listeria spp.…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotic resistance in E. coli is of particular concern because it is the most common Gram-negative bacterial pathogen causing intestinal and extra-intestinal infections in humans [ 48 ]. Apart from Gram-negative bacterial pathogens, fresh produce contaminated with Gram-positive bacteria, such as Listeria spp.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the present study, higher rates have been reported in the literature for the prevalence of E. coli in dairy products. For example, the prevalence rate was estimated at 52.4% (11/21 samples) in China [ 34 ] and 68.7% (103/150 samples) in Iran [ 40 ]. The findings of the present study regarding the presence of E. coli in packaged and pasteurized dairy products revealed that the prevalence of E. coli in pasteurized dairy samples was 6.7% (6/90 samples), which is in line with the prevalence of pasteurized dairy products reported by Rosario et al in 2021 (9/138, 6%) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inoculated plates of all pathogenic E. coli isolates were incubated aerobically at 37 °C for 18–24 h. Besides, E. coli ATCC25922 was used as a quality control strain. Finally, multidrug resistance (MDR) was considered as resistance against at least 3 or more classes of antibiotic agents [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pathogenic, and particularly Shiga-toxigenic E. coli strains have been identified in seafood products and their production environment including shellfish, raw and ready-to-eat fish and retail shrimp [29][30][31][32][33][34][35][36][37]. The coexistence of virulence/pathogenicity genes and ARGs has been demonstrated in several studies of E. coli isolated from the aquatic environment and seafood [38][39][40][41][42][43][44][45].…”
Section: Description Of the Amr Food Safety Issuementioning
confidence: 99%